De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Female masculinity - Halberstam, Jack (J.) (Duke University Press, 1998)
Dans cet ouvrage essentiel de la théorie queer, Jack Halberstam s’attaque au statut protégé de la masculinité masculine et montre que la masculinité féminine lui offre une alternative distincte depuis plus de deux siècles. Démontrant que la masculinité féminine n’est pas une mauvaise imitation de la virilité, mais une mise en scène vivante et dramatique de genres hybrides et minoritaires, Halberstam catalogue la diversité des expressions de genre chez les femmes masculines, depuis les pratiques pré-lesbiennes du XIXe siècle jusqu’aux performances contemporaines des drag kings.
Keywords: amériques; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; queer; régions géographiques; sciences humaines; thématiques; états-unis

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Queer theory: an introduction - Jagose, Annamarie (New York University Press, 1996)
The essential history of queer theory The reclamation of the term queer over the last several decades marked a shift in the study of sexuality from a focus on supposedly essential categories such as gay and lesbian, to more fluid notions of sexual identity. On the cutting-edge of this significant shift was Annamarie Jagose’s classic text Queer Theory: An Introduction. In this groundbreaking work, Jagose provides a clear and concise explanation of queer theory, tracing it as part of an intriguing history of same-sex love over the last century. Blending insights from prominent theorists such as Judith Butler and David Halperin, Jagose illustrates that queer theory's challenge is to create new ways of thinking, not only about fixed sexual identities such as straight and gay, but about other supposedly immovable notions such as sexuality and gender, and man and woman. First released almost 25 years ago, this groundbreaking work has provided a foundation for the continuing evolution of queer theory in the twenty-first century.
Keywords: approches et analyses; cours; discipline; histoire; premier cycle; queer; sciences humaines; soc2014; thématiques